Elaboración de un manual de procedimientos en higiene y seguridad del trabajo para los factores identificados como críticos en el Departamento Ambiental del Gadmic-Saquisilí, 2020-2021. - Pérez Garzón, Mario Ronaldo (2021)
The present investigation of the Elaboration of a Manual of Procedures in Occupational Hygiene and Safety for the control of risks in the facilities and activities of the Gadmic-Saquisilí that is located in the Province of Cotopaxi, Canton Saquisilí, Zone 3. The study indicates the problem that refers to the limitations of the control of risk factors that can affect the safety and health of the personnel in their jobs. This investigation is drafted in a precise way, making it possible to know the causes and consequences that are causing the conflict, in reference to the lack of an Occupational Health and Safety System. The problem corresponding to the lack of training of personnel in Risk Management is evident because it can be seen that they apply inadequate methods to identify risks, terrible ways of carrying out their municipal cleaning work and strategies in terms of Security and Occupational Health, by the senior environmental management, causing work accidents or obvious occupational diseases, such as covid-19 in this case. The research is relevant because it aims to improve occupational health and safety in all activities of the Gadmic-Saquisilí environment department.